PSV-28 Effect of a neuro-sensory additive on meat quality of feedlot finishing beef cattle - Desrousseaux, Guillaume (J Anim Sci, 2019)
Combining natural additives with specific and selected neuro-sensory molecules is a possible solution to manage stress in feedlot beef cattle. The objective of this study was to assess the use of a neuro-sensory additive (VeO) on meat quality of finishing feedlot beef cattle. This study was conducted from May to August in the Premix Research Center, Patrocínio Paulista, Brazil. VeO is based on a specific extract from Rutacea family. 80 Nellore bulls were randomly assigned to a control group (C) and a treated group (V) with 40 animals in each (10 per pen). Both groups received the same total mixed ration supplemented with Fator P (Premix, Brazil) with the addition of VeO as the only difference for 100 days up to slaughter. 160 cuttings in Longissimus muscle were sampled from C carcasses and V carcasses (n = 20) and packed in PVC blister packs 48h post-mortem. Analyzed variables were red color (a*), yellow color (b*) and drip losses (%) at packing then 3 days, 5 days and 7 days after. Statistical analysis was performed through mixed procedure of SAS software. Interactions between treatment and time was observed for values a* (P = 0.003) and b* (P = 0.056) and drip losses as well (P = 0.03). Globally meat from animals fed VeO presented more stable red and yellow colors. From day 5, it presented more intense red and yellow colors in comparison to meat from control animals. At day 7 drip losses were reduced with treatment (V: 8.7% vs. C: 11.4%, P = 0.012). Results showed that the use of the neuro-sensory additive during finishing of feedlot beef cattle improved appearance of meat after slaughter, leading to possible extended shelf life.